2021
DOI: 10.1109/access.2021.3057715
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Speech Testing for Symptom Assessment in Rapid Eye Movement Sleep Behavior Disorder and Parkinson’s Disease

Abstract: Speech impairment in Parkinson's Disease (PD) has been extensively studied. Our understanding of speech in people who are at an increased risk of developing PD is, however, rather limited. It is known that isolated Rapid Eye Movement (REM) sleep Behavior Disorder (RBD) is associated with a high risk of developing PD. The aim of this study is to investigate smartphone speech testing to: (1) distinguish participants with RBD from controls and PD, and (2) predict a range of self-or researcheradministered clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 50 publications
1
22
0
3
Order By: Relevance
“…As opposed to other types of speech signals that are often used in clinical assessments, such as running speech and reading aloud a linguistically rich pre-specified text e.g., the Grandfather Passage [20], the use of sustained phonations helps circumvent challenges associated with different accents and linguistic confounds [20]. For example, our previous work has shown that sustained phonations can provide high accuracy in differentiating PwP from controls [10], along with other interesting insights in the speech-PD literature, including replicating PD symptom severity and assisting PD rehabilitation [10,12,18,21]. We emphasize also that the methodology adopted in this study for processing sustained vowels had previously also been generalized to analyze different types of speech, e.g., voice fillers [42], and to provide useful insights more widely in different biomedical speech signal processing applications [43].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As opposed to other types of speech signals that are often used in clinical assessments, such as running speech and reading aloud a linguistically rich pre-specified text e.g., the Grandfather Passage [20], the use of sustained phonations helps circumvent challenges associated with different accents and linguistic confounds [20]. For example, our previous work has shown that sustained phonations can provide high accuracy in differentiating PwP from controls [10], along with other interesting insights in the speech-PD literature, including replicating PD symptom severity and assisting PD rehabilitation [10,12,18,21]. We emphasize also that the methodology adopted in this study for processing sustained vowels had previously also been generalized to analyze different types of speech, e.g., voice fillers [42], and to provide useful insights more widely in different biomedical speech signal processing applications [43].…”
Section: Discussionmentioning
confidence: 99%
“…We have used three state-of-the-art statistical mapping algorithms: (1) Random Forests (RF) [34], (2) Support Vector Machines (SVM) [35], (3) Adaptive Boosting (AdaBoost) [36] to tackle the binary differentiation problem in the study. We chose these methods as they are commonly used off-the-shelf classifiers that have been shown to be accurate in diverse supervised learning problems and, in particular, in a similar context differentiating PwP from controls using voice [18,19,25]. For the RF we explored optimizing performance using Breiman's recommendation with half and twice the default recommended number of features over which to select features for each node, and explored findings using 500 trees and 1000 trees.…”
Section: Statistical Mappingmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, touchscreen typ-ing pattern analysis has been used for early detection of finemotor impairment [13], whereas accelerometer-based analysis was employed for tremor detection [14], expressing the effect of PD to upper-extremity motor function of PD patients. Use of speech recordings through smartphone devices of participants enrolled in conducted studies have been used on [25], [26], where authors used a feature-space that represents the key aspects of hypokinetic dysarthria in the early stages of PD, indicating that early screening is possible via acoustic segment analysis. The current work acts as an extension to the previous approaches by focusing on voice-related passive data collection captured during phone calls via the iPrognosis app.…”
Section: Introductionmentioning
confidence: 99%